PENGARUH GADJET TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DAN BUDI PEKERTI KELAS VIII SMP N 2 CERENTI - Musinah Musinah; Sopiatun Nahwiyah; Helbi Akbar (JOM FTK UNIKS (Jurnal Online Mahasiswa FTK UNIKS), 2022)
This research is motivated by the influence of gadget on student learing outcomes. Islamic religious education is one of the that subjects that are less attractive to students, so they become bored, passive,and lazy to think actively in learning. This study aims to determine the effect of gadget on student learning outcomes in the subjects of Islamic religious education and character in class VIII SMP N 2 Cerenti. This research is a quantitative research. The population in this study were all students of class VIII. Data collection teachiques were observation, interviews and documentation. The data analysis teachnique used the ‘’t’’ test with the help of SPSS which previously carried out the prerequisite analysis test. The results of the t-test showed a significant difference between class using gadgets and those not using gadgets. Based on the results of the study, it can be concluded that there is an effect of studentslearning outcomes on gadgets. Based on the results of this study, the aim of this study was to determine whether there an influence of gadgets on students learning outcomes in Islamic religious education subjects and students character at SMP N 2 Cerenti. this research is a quantitative study whose data are in the form of numbers and analysis using statistics. which was held at SMP N 2 Cerenti. The results showed that there was an influence of gadgets on student learning outcomes in the subjects of Islamic religious education and manners at SMP N 2 Cerenti, Kuantan Singing regency. the results of this study are the learning outcomes of students who are taught by those who do not use gadgets in the material to closer to by praying in class VIII get an average score of 60,5%. meanwhile,students laering outcomes who are taught using gadgets gat an average score of 80,5%.